Gilbert syndrome in patients with inherited hemolytic anemia modifies the clinical phenotype - Anika Agrawal; Jagdish Chandra (Elsevier, 2024)
Gilbert syndrome is a benign condition due to UGT1A1 mutations frequently resulting in mild, indirect hyperbilirubinemia. Inherited hemolytic anemias often present with hyperbilirubinemia and hepatosplenomegaly. Over the years, there have been multiple case reports/series in which the extent of unconjugated hyperbilirubinemia exceeds the extent of anemia. When worked up for the unexplained hyperbilirubinemia, these patients were found to carry mutations corresponding to both immune hemolytic anemia as well as Gilbert syndrome. This article aims to emphasise when to suspect this coexistence and how to approach a patient with inherited hemolytic anemia with unexplained jaundice.